The Chronic Effects of Sodium Chloride on the Some Reproductive Parameters of the Crustaceans Daphnia pulex (Crustacea: Claclocera) - S.F. Bassat; Z.N. Al-Azawi (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
This study included the effect of chronic exposure of different concentrations of sodium chloride on the freshwater Crustacean Daphinea pulex from the order of Cladocera. The concentrations used for the chronic exposure were( 0.1‰, 0.5‰, 1‰, 1.5‰, 2‰ )to investigate the effect on the some reproductive parameter which included mean number of eggs and juveniles produced per female and per clutch,and mean number of clutch per female which decline from (6.0) clutch/female in the control treatment to (3.0) clutch/female in (2‰) concentrations, as well as to investigate the number of females produce the clutches and we found only one female produced six cluthes in the( 2‰) concentration of sodium chloride .Increasing of sodium chloride concentrations coincidence with increasing of time intervals of eggs appearance in the broadpouch as well as increasing in the time intervals between cluthes when salt concentrations increase.